Elitesportslig succes i Danmark og udlandet - en analyse - Westhausen, G. M. (2014)
This aim of this master thesis is to explore and answer the following main -and sub-questions: What determine Danish elite sporting success, and how can Denmark boost its success compared to other countries in SPLISS cooperation? • How does one measure elite sporting success? • What so cial value does Danish elite sport has? After a brief review of the historical development and impacts on elite sport , the Danish sport structure and economy are being analyzed . Further the method for measuring elite sporting success in Denmark is being analyzed . Finally, the preliminary results from recent the SPLISS 2.0 study (Sports Policy Factors Leading to International Sporting Success) are being analyzed from a critical rationalistic approach in order to find out , what determine Danish elite sporting success compared to the other countries that are involved in the SPLISS study .The theoretical framework consists of the SPLISS model, which has included sport policy factors that may cause to international elite sporting success. These are not all the factors that come into play in relation to elite sporting success. The literature reveals that more than 50% of the determinants of international elite sporting success are macro-level variables, which are beyond the control of politicians. However, the SPLISS model consists of 9 "pillars": Pillar 1 financial support, pillar 2 organization and structure of sport policies, pillar 3 foundation and participation, pillar 4 talent identification and -development system, pillar 5 athletic and post-career support, pillar 6 training facilities, pillar 7 coaching provision and coach development, pillar 8 international competition and pillar 9 scientific research. The model indicates that elite sport should be evaluated at three stages. First stage is inputs that are reflected in pillar 1. If nations do not have the means to invest in elite sport development, chances of success are small. Second stage is throughputs, which is the support and systems delivered to the athletes, coaches and organizations at each stage of the development process. The pillars 2 -9 are an indicator of the through -put stage. Third stage is the outputs in relation to elite sport this is the actual performance, which can be defined in absolute or relative terms. The SPLISS model can be used as a method to measure and especially compare different nations' competitive position in elite sport by looking at how each nation are ranked in relation to the respective "pillars". On the basis of the Danish elite sport success, structure etc. this paper pro vides an overview of importa nt determinants that can lead the nation to enjoy international sporting success by comparing it to the rest of 14 nations that are attending the SPLISS study 2.0.